2021
DOI: 10.9734/jpri/2021/v33i1231252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hirsutism among Females with Chronic Obstructive Pulmonary Disease and Hyperthyrodism at Tertiary Care Hospital of Sindh, Pakistan

Abstract: Introduction: Hirsutism is in fact unwanted growth of hairs on the various parts of body of females. Hairs arises particularly on those parts of the body on which hairs are not grown normally in females such as chin, upper lips, abdomen, legs, shoulder and back of the body. Various reasons are reported till so far for the hirsutism development. The prevalence of hirsutism was very low. Methodology: Across-sectional study was conducted at tertiary care hospital of Sindh, Pakisan for the period of 06 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Anjum et al 12 demonstrated it 38% in comparison to PCOS related hirsutism 58% and according to Ansarin et al 13 , 35.2% IH prevalence was found in comparison of 62.5% of that related to PCOS. Huma et al 14 , in a medical clinic has reported the prevalence of idiopathic hirsutism as 53%. So we are not justified in dealing every hirsute case as PCOS, rather idiopathic causes should also be considered and associations be addressed to manage this problem in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anjum et al 12 demonstrated it 38% in comparison to PCOS related hirsutism 58% and according to Ansarin et al 13 , 35.2% IH prevalence was found in comparison of 62.5% of that related to PCOS. Huma et al 14 , in a medical clinic has reported the prevalence of idiopathic hirsutism as 53%. So we are not justified in dealing every hirsute case as PCOS, rather idiopathic causes should also be considered and associations be addressed to manage this problem in our patients.…”
Section: Discussionmentioning
confidence: 99%